O46: PERIOPERATIVE LIQUID BIOPSY MAY HELP PREDICT THE RISK OF RECURRENCE IN BREAST CANCER PATIENTS. (27th April 2021) - Hassan, F; O'Leary, DP; Ita, M; Corrigan, M; Wang, JH; Redmond, HP
Abstract: Introduction: Liquid biopsy analysis using cell-free DNA (cfDNA) and circulating tumour DNA (ctDNA) has emerged as a promising non-invasive technique to detect fragmented circulating tumour DNA. It has shown excellent diagnostic and prognostic potential in breast cancer. Here, we aimed to evaluate the peri-operative dynamics of cfDNA and ctDNA to determine their prognostic ability in breast cancer. Method: Breast cancer patients undergoing curative surgery were included. Blood samples were taken pre-operatively and 30 days post-operatively. cfDNA was extracted and measured using spectrophotometry. DNA integrity (long/short DNA fragments) was measured using ALU247 and ALU115 primers. PIK3CA mutation at exon 9 and 20 in ctDNA was detected using high resolution melting (HRM) real-time PCR combined with parallel internal controls. Ethical approval was granted. Result: A total of 29 patients were studied, 14 disease-free group (DF) and 15 disease recurrence group (DR). The median follow-up was 36 months. cfDNA concentrations and DNA integrity were significantly higher in DR group compared to the DF group pre-operatively (cfDNA concentrations, p=0.0004; DNA integrity, p=0.039) and at 30 day post-operative time period (cfDNA concentrations, p=0.04; DNA integrity, p=0.03). Higher post–operative cfDNA concentrations were predictive of poor disease-free survival (HR: 3.8, p=0.02). Post-operative PIK3CA mutation detection in ctDNA was associated with a higher risk of recurrence (Odds ratio: 1.86, 95% CI: 0.36-12.9). Conclusion: cfDNA and ctDNA assessment can provide valuable prognostic information at the time of surgery and have the potential to stratify the risk of recurrence and allow more personalised follow-up plan in breast cancer patients. Take-home message: Liquid biopsy is a non- invasive and easily reproducible blood test that can provide important prognostic information at 30 days following surgery and may help clinicians to predict which breast cancer patients are at higher risk of recurrence following surgery.